Penggunaan Aplikasi “Baca Mandiri” Dalam Mengatasi Kesulitan Membaca Permulaan Pascapembelajaran Daring - Rofikoh Sulistiani; Iswara, Prana Dwija; Nugraha, Dadan (Journal for Lesson and Learning Studies, 2023)
Implementing online learning during the pandemic prevented students from receiving intensive early reading lessons at school. This ultimately resulted in the difficulty of class II in reading the beginning. The focus of this study was to analyze the effect of using the Baca Mandiri application on students' initial reading ability. This study used a pre-experimental method with the One Group Pretest-Posttest Design model with a sample of 13 students from a two-class population of 55 students who had problems with initial reading mastery. Data was collected by pretest and post-test to measure students' initial reading ability. In addition, the questionnaire instrument was used to explore respondents' responses, namely students and teachers, regarding using the Baca Mandiri application in early reading learning. Hypothesis testing is carried out using nonparametric statistics, namely the Wilcoxon Test. The pretest and post-test results increased, with an average pretest score of 56.29. After students were given treatment using the Baca Mandiri application, the average post-test score of students increased to 72.90. This study concludes that the use of Baca Mandiri application media significantly affects students' beginning reading abilities. The results of this study reinforce suggestions for using electronic applications in learning, especially in beginning reading in the lower grades. The use of application has the potential to be used by students independently in the future.